Medical complications of homelessness: a neglected side of men's health. Issue 4 (7th April 2019) - Brown, Mark A.; Gellatley, Wendy; Hoffman, Anna; Dowdell, Lisa; Camac, Anne; Francois, Rachel; Boston, Belinda; Zekry, Amany
Abstract: Background: Homelessness is an increasing societal and health issue associated with high rates of substance abuse and mental health disorders. Homeless people die more often and at a younger age than others. Aim: To identify health needs and improve healthcare for homeless men. Methods: A physician‐led clinic was established on‐site at the Mission Australia Centre in Sydney, incorporating: (i) liver screening, including portable fibroscan testing, and on‐site treatment of hepatitis C; (ii) a mental health clinic, staffed by a psychiatrist; and (iii) a nurse‐led clinic to follow up medical issues and deliver vaccinations. Patient data were recorded prospectively to determine what medical problems were encountered so as to drive future healthcare planning. Results: A total of 257 men was assessed between November 2011 and December 2017. In that time, 561 men resided at the Centre. Of these 257 men who attended the clinic, 61% were <45 years old; 69% were current and 8% former smokers; 62% had a history of chronic alcoholic abuse and 66% other substance abuse; 64% had one or more of depression, anxiety, psychosis or another mental health disorder and 44% had metabolic syndrome features, 38% cardiovascular disease, 29% hepatitis C and 21% a respiratory disorder. Conclusion: The main health needs of homeless men fall into the categories of mental health; cardiovascular, respiratory and metabolic disorders and addictions and hepatitis C. Establishing on‐site clinics at homeless shelters with expertise to address these issues will likely improve the well‐being of these men, reduce hospital admissions and prolong their lives.